Discipline with dignity [ new challenges, new solutions - Curwin, Richard L. , 1944-; Mendler, Allen N.; Mendler, Brian D. (Gale virtual reference library, 2008)
Offers practical solutions that focus on relationship building, curriculum relevance, and academic success. Emphasizes the prevention of problems by helping students to understand each other, work well together, and develop responsibility for their own actions. Also includes intervention strategies for handling common and severe problems in dignified ways